The Relationship of Lifting Position with Low Back Pain Complaints Based on the National Institute for Occupational Safety and Health (NIOSH) Lifting Equation in Transport Workers at Kalimas Port Manado - D. E. Purba, Yohana; Lintong, Fransiska; F. Rumampuk, Jimmy; E.W. Moningka, Maya; R. Danes, Vennetia (Jurnal KESANS : Kesehatan dan Sains, 2024)
Introduction: Low back pain is one of the health problems that is often experienced by workers, especially in transport workers who often do heavy lifting. According to WHO, low back pain occurs in 2% to 5% of employees in developed countries every year and causes 15% of work absenteeism, especially in the steel industry and trade sectors. Objective: The purpose of this study was to determine the relationship between weight lifting position and low back pain complaints based on the NIOSH Lifting Equation in transport workers at Kalimas Port Manado. Methods: The study was conducted with observational analytic research using cross sectional design. Then analysed using IBM SPSS software with spearman statistical test. Results: The results showed that most workers experienced low back pain with varying intensity. A significance value of 0.044 (p<0.05) was obtained. Conclusion: There is a relationship between the position of lifting the load with complaints of low back pain based on the NIOSH Lifting Equation in transport workers at Kalimas Port Manado